CLIL methodology, materials and resources, and assessment in a monolingual context: an analysis of stakeholders' perceptions in Andalusia. Issue 1 (2nd January 2020) - Barrios, Elvira; Milla Lara, María Dolores
ABSTRACT: This paper presents an investigation into stakeholder perspectives on the methodology, materials and resources and assessment procedures employed in a bilingual (CLIL) programme in a monolingual context. A total of 873 respondents (544 students, 92 teachers and 237 parents) in Andalusia, Spain (more specifically, in the provinces of Málaga and Cádiz) took part in the study. Questionnaires and focus groups were used to gauge stakeholder perspectives on important curricular issues, which were then interpreted within the framework of a SWOT (strengths, weaknesses, opportunities and threats) analysis. The most commonly reported methodological strength of the programme was its use of innovative pedagogical practices, which seem to be spreading from the CLIL programme into the mainstream programme. Inadequate teacher training in the CLIL methodology was the most commonly reported weakness by teachers. To provide a more comprehensive picture of stakeholders' views of the programme between-group comparisons were also performed. These indicated that there were group differences in perceptions of numerous CLIL-related issues, which emphasises the need to pay attention to how the different groups involved interpret the CLIL educational experience.